Voices of the dying and bereaved : music therapy narratives - Clements-Cortés, Amy; Klinck, Sara Varvas (Barcelona Publishers, 2016)
"This books presents valuable information on the role of music therapy with respect to a number of issues common to end-of-life care and bereavement with a focus on grief and loss. The purpose of the book is to provide information and examples of ways of working in music therapy with the dying and bereaved for students, professional music therapists, as well as those in related healthcare roles and companions on the journey of the dying. The co-authors practice in an eclectic model of music therapy that is humanistic and client - entered at its core. Part one provides a thematic review of literature describing the use of music in end-of-life care, as well as a summary of music therapy techniques commonly implemented in these environments. This is followed by the presentation of 3 case study chapters based on Clements-Cortes' work in palliative care. Each chapter is completed with a link back to the emerging themes in end-of-life care as outlined in chapter one. Part two presents a thematic review of literature describing the use of music in bereavement, and is followed by 3 case study chapters based on Klinck's work in bereavement care, illustrating the narrative experiences of her research study participants. Part two concludes with the presentation of an author developed Music Therapy Bereavement Group Model. Case studies are presented in narrative format, and in this way honor the voices of the dying and bereaved and fully illuminate the therapeutic process in work towards client identified goals."--Publisher's description.